Frequency Coded Chipless RFID Tag using Spurline Resonators - M. Sumi; R. Dinesh; C. M. Nijas; S. Mridula; P. Mohanan (Radioengineering, 2014)
A novel compact chipless RFID tag using spurline resonators is discussed in this paper. The detection of the tag's ID is using the spectral signature of a spurline resonator circuit. The tag has a data capacity of 8-bits in the range 2.38 to 4.04 GHz. The tag consists of a spurline multiresonating circuit and two cross polarised antennas. The prototype of the tag is fabricated on a substrate C-MET/LK4.3 of dielectric constant 4.3 and loss tangent 0.0018. The measured results show that group delay response can also be used to decode the tag’s identity.